2022
DOI: 10.14740/jocmr4813
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience With Quadratus Lumborum Catheters for Postoperative Pain Management in Pediatric-Aged Patients With Contraindications to Epidural Anesthesia

Abstract: Background: Although neuraxial techniques such as caudal and epidural anesthesia were initially the predominant regional anesthetic technique used to provide postoperative analgesia in children, there has been a transition to the use of peripheral nerve blockade such as the quadratus lumborum block (QLB). We present preliminary experience with QL catheters for continuous postoperative analgesia in a cohort of pediatric patients following colorectal surgery.Methods: After institutional review board (IRB) approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ropivacaine hydrochloride is the most widely used local anesthetic for nerve block in the clinic at present, and the concentration used in the clinic varies from 0.1 to 1%. [18][19][20] Because the sciatic nerve of C57BL/6 mice is thinner than the peripheral nerve of humans and direct incision injection is more intuitive than puncture injection, it is not easy to cause mechanical damage to the peripheral nerve. A previous study found that local anesthetics cause significant neurotoxic damage to developing neurons, and the concentration and exposure time of local anesthetics are important factors for nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…Ropivacaine hydrochloride is the most widely used local anesthetic for nerve block in the clinic at present, and the concentration used in the clinic varies from 0.1 to 1%. [18][19][20] Because the sciatic nerve of C57BL/6 mice is thinner than the peripheral nerve of humans and direct incision injection is more intuitive than puncture injection, it is not easy to cause mechanical damage to the peripheral nerve. A previous study found that local anesthetics cause significant neurotoxic damage to developing neurons, and the concentration and exposure time of local anesthetics are important factors for nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter placement can be unilateral or bilateral depending on indication, and would also serve to avoid some of the potential complications associated with instrumentation of the neuraxial space. Preliminary data suggest that quadratus lumborum catheters provide prolonged analgesia following colorectal procedures with no adverse effects noted other than early inadvertent catheter removal [13 ▪ ]. There are also promising data regarding decreased opioid consumption for adult patients undergoing bone marrow biopsies who receive quadratus lumborum blocks [14 ▪ ].…”
Section: Paediatric Regional Anaesthesiamentioning
confidence: 99%